Step-scheme CdS/TiO2 nanocomposite hollow microsphere with enhanced photocatalytic CO2 reduction activity. (1st November 2020) - Wang, Zhongliao; Chen, Yifan; Zhang, Liuyang; Cheng, Bei; Yu, Jiaguo; Fan, Jiajie
Graphical abstract: Highlights: The successful preparation of CdS/TiO2 hollow microspheres. The investigation of CdS/TiO2 hollow microspheres with various molar ratio. The strong redox ability of charge carriers in the step-scheme mechanism. High photocatalytic CO2 reduction activity of CdS/TiO2 hollow microspheres. Abstract: Converting solar energy into chemical energy by artificial photosynthesis is promising in addressing the issues of the greenhouse effect and fossil fuel crisis. Herein, a novel photocatalyst, i.e. CdS/TiO2 hollow microspheres (HS), were dedicatedly designed to boost overall photocatalytic efficiency. TiO2 nanoparticles were in-situ decorated on the inside and outside the shell of CdS HS, ensuring close contact between TiO2 and CdS. The CdS/TiO2 HS with abundant mesopores inside of the shell boost the light absorption via multiscattering effect as well as accessible to reactions in all directions. The heterojunction was scrutinized and the charge transfer across it was revealed by in-situ irradiated X-ray photoelectron spectroscopy (ISI-XPS). Ultimately, the charge transfer in this composite was determined to follow step-scheme mechanism, which not only facilitates the separation of charge carriers but also preserves strong redox ability. Benefited from the intimate linkage between CdS and TiO2 and the favorable step-scheme heterojunction, enhanced photocatalytic CO2 reduction activity was accomplished. The CH4 yield rate of CdS/TiO2 reaches 27.85 μmol g –1 h –1, which is 145.6 and 3.8 times higher than those of pristine CdS and TiO2, respectively. This work presents a novel insight into constructing step-scheme photocatalytic system with desirable performance.